Micromechanics of Materials, with Applications - Kachanov, Mark (Solid Mechanics and Its Applications, 2018)
This book on micromechanics explores both traditional aspects and the advances made in the last 10-15 years. The viewpoint it assumes is that the rapidly developing field of micromechanics, apart from being of fundamental scientific importance, is motivated by materials science applications. The introductory chapter provides the necessary background together with some less traditional material, examining e.g. approximate elastic symmetries, Rice's technique of internal variables and multipole expansions. The remainder of the book is divided into the following parts: (A) classic results, which consist of Rift Valley Energy (RVE), Hill's results, Eshelby's results for ellipsoidal inhomogeneities, and approximate schemes for the effective properties; (B) results aimed at overcoming these limitations, such as volumes smaller than RVE, quantitative characterization of "irregular" microstructures, non-ellipsoidal inhomogeneities, and cross-property connections; (C) local fields and effects of interactions on them; and lastly (D) - the largest section - which explores applications to eight classes of materials that illustrate how to apply the micromechanics methodology to specific materials.